Presenting a structural model of school connectedness based on social- academic boredom with the mediating role of alexithymia in highschool students - Melika Salehi Afshar; Akbar Mohammadi; Sara Haghighat (مجله علوم روانشناختی)
making schools a significant influence on students. The relationships formed in classrooms with teachers and peers can profoundly impact adolescents' social outcomes and educational experiences. Aims: This research aimed to present a structural model of school connectedness based on academic boredom, with a focus on the mediating role of alexithymia among high school students. Methods: This study employed a cross-sectional correlational research design. The statistical population included all second-level high school students in Tehran during the academic year 2021-2022, with 341 participants’ selected using cluster random sampling. The study utilized measures for School Connectedness (Brown & Evans, 2002), Academic Boredom (Fraser et al., 1995), and Alexithymia (Toronto, 1994). Data analysis was conducted using SPSS-V23 and Lisrel-V8.8 software, with structural equation modeling used to test the research hypotheses. Results: The research findings indicated a good fit of the proposed model. The results revealed a significant total path coefficient (p= 0.001, β= -1.39) between academic boredom and school connectedness. This suggests a relationship between secondary-level students' school connectedness, academic boredom, and alexithymia mediation. Conclusion: The study recommends enhancing coordination between counseling centers and school counselors to foster stronger school connectedness, reduce academic boredom, and address emotional challenges among students. Paying attention to these variables can aid researchers and therapists in developing preventive measures and more effective interventions.